2008
DOI: 10.1007/s12119-008-9029-7
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background

Abstract: We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 29 publications
(80 reference statements)
1
44
0
1
Order By: Relevance
“…These questions have simply been elided in most research on the subject. Several scholars, however, note the influence of the Sexual Revolution of the late 1960s and 1970s, in particular a general increase in sexual permissiveness (Bogle 2008;England et al 2008;Harding and Jencks 2003) and widespread availability of birth control (Fugere et al 2008). Others have pointed to the Women's Movement's push for acceptance of casual and non-marital sex for women (Bogle 2008;Fugere et al 2008).…”
Section: Hypotheses For the Causes And Timing Of Hook-up Culturementioning
confidence: 99%
See 1 more Smart Citation
“…These questions have simply been elided in most research on the subject. Several scholars, however, note the influence of the Sexual Revolution of the late 1960s and 1970s, in particular a general increase in sexual permissiveness (Bogle 2008;England et al 2008;Harding and Jencks 2003) and widespread availability of birth control (Fugere et al 2008). Others have pointed to the Women's Movement's push for acceptance of casual and non-marital sex for women (Bogle 2008;Fugere et al 2008).…”
Section: Hypotheses For the Causes And Timing Of Hook-up Culturementioning
confidence: 99%
“…Some scholars have suggested that access to pornography via the Internet spurred hook-up culture (Fugere et al 2008;Garcia and Reiber 2008). Internet access accelerated starting in the mid-1990s as personal computer ownership became more affordable.…”
Section: Access To and Consumption Of Pornographymentioning
confidence: 99%
“…The impact of gender on assessments of the sexual double standard may be related to participants' personal attitudes towards sexuality; participants who endorse liberal attitudes towards sexuality may not conform to traditional sex-and age-based scripts and norms of behavior, and sexual attitudes are typically more liberal among men than women, although effect sizes are typically small (Fugère et al 2008). Those who have more positive attitudes towards sex generally have more positive attitudes to a wider range of sexual behaviours and may therefore perceive more interest in traditional and experimental sex among all targets.…”
Section: Individual Differences In Endorsements Of Sexual and Ageist mentioning
confidence: 99%
“…This is surprising given racial and ethnic differences in attitudes surrounding the engagement in sexual behaviors (Cuffee, Hallfors, & Waller, 2007; Fugère, Escoto, Cousins, Riggs, & Haerich, 2008), as well as the changing diversity of the United States (Jones & Bullock, 2013). Recent studies that utilize more diverse samples find that Black youth are significantly more likely to report experience with vaginal sex compared to their White counterparts (Burdette & Hill, 2009).…”
Section: Introductionmentioning
confidence: 99%